Analysis of Energy Reduction and Energy Self-Sufficiency Improvement Effects by Applying a Bidirectional Reflectance PV Array with Integrated External Shading at a School Building - Keon Ho Lee; Young-Hak Song (Buildings, 2023)
In South Korea, the introduction of new and renewable energy in the building sector has been promoted through various policies since the early 2000s. As a result, solar photovoltaics (PV), which are mostly applied to the rooftops of buildings, and building-integrated photovoltaics (BIPV), which are installed on the elevated surfaces of buildings, have been applied to various sites with subsidies. Renewable energy will be mandatory for all buildings from 2025. In general, the power generation efficiency of PV panels varies depending on the installation angle. According to Korean standards, the power generation efficiency is 100% for an installation on a 30° slope, 90% for a horizontal installation, and 70% for a vertical installation. This study proposes a BIPV that improves the power generation efficiency using the unique reflectance of PV panel surfaces made of glass and a bidirectional reflectance PV array. This new type of BIPV structure improves the power generation efficiency and reduces the solar heat gain coefficient (SHGC) as it protrudes over the windows, providing external shading. It is defined as bidirectional reflectance PV (BRPV), and its performance is evaluated. The effects of applying BRPVs (48 KW by 160 PV Panels with 300 W) to a school building with a fixed slope PV on the rooftop were calculated based on annual measurement results, and it was found that the energy independence rate of the building increased from 34.1 to 65.8%.